Reformist Muslim Discourse in the Sundanese Commentary of the Qur’ān: E. Abdurrahman’s Commentary on QS. Al-Hujurāt - Roni Nugraha; Jajang A Rohmana (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2021)
This article focuses on reformist Muslim discourse in the Sundanese commentary of the Qur’ān or tafsīr, entitle Sababaraha Naséhat Tina Qur’an Surat al-Hudjurot, some advice of sūrah Al-Hujurāt (1971). The book was written by E. Abdurrahman (1912-1983), an activist of a reformist Islamic organization, Islamic Union (Persatuan Islam or Persis). He has been a chairman of Persis from 1962-1983. They have a slogan “back to the Qur’ān and Hadīth” as well as to oppose the taqlīd and heresy. E. Abdurrahman explained Q. 49 or sūrah Al-Hujurāt in the frame of his ideology as an activist of Persis. Following his commentary of Q. 49:1, the prohibition against practicing Islam before find dalīl or textual instructions of the Qur’ān and Hadīth. He also interpreted Q. 49:6 on recheck the news as a form of prohibition taqlīd. Meanwhile, Q. 49:9-10 was interpreted by him to emphasizes the strengthening of reformist followers. Using Fairclough’s critical discourse analysis, this study confirms that E. Abdurrahman’s commentary cannot be separated from his reformist ideology. He used Sundanese Quranic commentary to convey the reformist ideas against traditionalist Muslims in West Java.